Gaps in the Continuum of HIV Care: Long Pretreatment Waiting Time between HIV Diagnosis and Antiretroviral Therapy Initiation Leads to Poor Treatment Adherence and Outcomes. (22nd December 2016) - Su, Shu; Li, Shifu; Li, Shunxiang; Gao, Liangmin; Cai, Ying; Fu, Jincui; Guo, Chunyuan; Jing, Jun; Chen, Liang; Mao, Limin; Cheng, Feng; Zhang, Lei
Abstract : Background. Criteria for antiretroviral treatment (ART) were adjusted to enable early HIV treatment for people living HIV/AIDS (PLHIV) in China in recent years. This study aims to determine how pretreatment waiting time after HIV confirmation affects subsequent adherence and outcomes over the course of treatment. Methods. A retrospective observational cohort study was conducted using treatment data from PLHIV in Yuxi, China, between January 2004 and December 2015. Results. Of 1, 663 participants, 348 were delayed testers and mostly initiated treatment within 28 days. In comparison, 1, 315 were nondelayed testers and the median pretreatment waiting time was 599 days, but it significantly declined over the study period. Pretreatment CD4 T-cell count drop (every 100 cells/mm 3 ) contributed slowly in CD4 recovery after treatment initiation (8% less, P < 0.01 ) and increased the risk of poor treatment adherence by 15% (ARR = 1.15, 1.08–1.25). Every 100 days of extensive pretreatment waiting time increased rates of loss to follow-up by 20% (ARR = 1.20, 1.07–1.29) and mortality rate by 11% (ARR = 1.11, 1.06–1.21), based on multivariable Cox regression. Conclusion. Long pretreatment waiting time in PLHIV can lead to higher risk of poor treatment adherence and HIV-related mortality. Current treatment guidelines should be updated to provide ART promptly.